The Effect of Training and Work Environment on Employee Performance with Job Satisfaction as Moderating Variable at PT Karsa Mulia Sejahtera Balikpapan - Muhammad Fernanda Fadilah; Nurul Asfiah; Kenny Roz (Universitas Muhammadiyah Malang, 2023)
The aim of this study is to determine if training and workplace environment have an impact on employee performance with job satisfaction acting as a moderating variable. This type of study employs a quantified approach and a 40-person sample size. Information was gathered by handing out surveys (primary data). The statistics in this research are examined using path analysis. According to research findings, training has a positive but not statistically significant effect on employee performance, job satisfaction has a positive and statistically significant effect on employee performance, and work environment has a positive and statistically significant effect on employee performance. However, job satisfaction is unable to moderate either of these effects on employee performance.